Criminal Responsibility For Perpetrators of Criminal Acts With Schizophrenic Mental Disorders - Adellia Eddiesa Putri; Bambang Waluyo (Journal of Law, Politic and Humanities, 2024)
Schizophrenia is a psychotic disorder that causes sufferers to experience hallucinations and delusions that affect their emotions, behavior, and way of thinking. The purpose of this research is to find out the legal responsibility in handling cases committed by people with mental disorders, and to find out how legal policies in deciding actions against perpetrators with mental disorders. This research uses a juridical-normative legal method with a statutory approach. From this research, it can be concluded that Article 44 paragraphs (1) and (2) of the Criminal Code as well as Articles 38 and 39 of Law No.1 Year 2023 can be the basis for judges in deciding the actions that can be given to offenders with mental disorders. The ability to be responsible is an important part of determining whether the perpetrator can be given a criminal offense or not, so the judge can call an expert witness to assess the behavior and mental health of the perpetrator as a consideration for the judge in deciding. If the perpetrator is declared to have a mental disorder, then the judge can consider the reasons for criminal erasure.